Hemodiafiltration versus conventional hemodialysis: Should "conventional" be redefined?. Issue 6 (29th May 2018) - Maduell, Francisco
Abstract: In the 1980s, conventional hemodialysis was considered as dialysis with acetate dialysate, dialysis machines without volumetric control, low blood flow and low‐flux dialyzers; in the 1990s, the concept of conventional hemodialysis changed due to technological advances in dialysis machines, control of ultrafiltration and the widespread use of bicarbonate dialysate, which allowed an increase in blood flow and the use of synthetic high‐flux dialyzers. To avoid backfiltration‐induced adverse reactions, exogenous replacement fluid was promoted but its adoption was limited for technical and financial reasons. This scenario changed in 1995 with the development of on‐line hemodiafiltration (HDF) techniques using the dialysis fluid itself as a replacement fluid. Dialysis machines were modified to perform on‐line HDF, incorporating safety filters to ensure the quality of this replacement fluid (ultrapure dialysate). After more than two decades of clinical experience and technological development with high‐volume HDF, the present article discusses whether HDF can currently be considered as the standard conventional treatment for chronic hemodialysis patients. A review of the evidence indicates that the time has come to consider HDF as the conventional hemodialysis treatment for the following reasons: first, technological development in water treatment and advances in dialysis machines, as well as the widespread use of synthetic high‐flux dialyzers has made it a feasible proposition. Second, there is an absence of published literature showing any undesirable effects. Finally, scientific evidence is available showing the superiority of HDF over hemodialysis in overall and cardiovascular mortality in both prevalent and incident patients.